Pentahelix synergy to women empowerment: analyzing stakeholder engagement in a CSR program PT Pertamina Patra Niaga DPPU Adisumarmo for village development - Rashifahunnisa' Mellinia; Siti Fatonah; Bintang Fajar Pamungkas (Global Research Network, 2024)
In the era of dynamic social and economic development, this study explores and analyzes the implementation of the Pentahelix model in a Corporate Social Responsibility (CSR) program run by PT Pertamina Patra Niaga DPPU Adisumarmo. With a primary emphasis on the nuanced roles and contributions of government, industry, academia, community, and media within the Pentahelix framework, the research centers around their collective efforts in propelling women's empowerment and fostering village development. The core objective is to unravel the multifaceted impact of this collaboration on women's empowerment and the holistic development of rural villages.Through an exhaustive analysis of stakeholder interactions and synergies, the study not only underscores the intrinsic importance of cross-sector collaboration but also reveals the nuanced ways in which it has been pivotal in ensuring the success of the CSR program. The discussion delves into the specific outcomes of this collaboration, shedding light on how it has propelled women's empowerment initiatives and catalyzed tangible advancements in rural development. By elucidating the complexities and interdependencies within Pentahelix, the research offers profound insights into how the amalgamation of diverse interests can yield substantial positive impacts, thereby contributing significantly to the sustainable development narrative.